2017
DOI: 10.2135/cropsci2016.12.0976
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Measurement and Genotype × Environment Interaction for Potato Specific Gravity

Abstract: Specific gravity (SpGr) is often used to measure the processing quality of potato (Solanum tuberosum L.) tubers for French fries or potato chips because of its strong correlation with dry matter content and ease of measurement. For French fry processing genotypes, the desirable range for mean SpGr is typically 1.080 to 1.095, and a small variance around the mean is essential for product uniformity. Two multi‐year, multi‐location trials were conducted to investigate the genetics of SpGr in elite russet germplas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…The analysis used linear mixed models with factor-analytic (FA) covariance structures to parsimoniously model the genetic correlation between many environments (Piepho, 1998;Smith et al, 2001). Factor-analytic models have been used before to analyze multienvironment trials of potato, including Paget et al (2015) for yield in New Zealand and Wang et al (2017) for specific gravity of russet potatoes in the United States. Both studies used the "uniplot" technique of Cullis et al (2010) to visualize genetic correlation with a second-order FA model.…”
mentioning
confidence: 99%
“…The analysis used linear mixed models with factor-analytic (FA) covariance structures to parsimoniously model the genetic correlation between many environments (Piepho, 1998;Smith et al, 2001). Factor-analytic models have been used before to analyze multienvironment trials of potato, including Paget et al (2015) for yield in New Zealand and Wang et al (2017) for specific gravity of russet potatoes in the United States. Both studies used the "uniplot" technique of Cullis et al (2010) to visualize genetic correlation with a second-order FA model.…”
mentioning
confidence: 99%
“…The G×E is commonly detected for SG and has already been described in other studies (Teixeira et al 2015, Wang et al 2017. Teixeira et al (2015) discussed the effect temperature has on the SG, where environments that had higher temperatures can cause a decrease in SG compared to environments with mild temperatures.…”
Section: Resultsmentioning
confidence: 71%
“…Lynch et al (1992) found high GCA effects and nonsignificant SCA effects for specific gravity and suggested that mainly additive genetic factors account for the genetic variation. Wang et al (2017) also showed relatively little genotype × environment interaction for specific gravity. Specific gravity as a proxy for dry matter content can be used for selecting chipping potatoes.…”
Section: Discussionmentioning
confidence: 98%